A study on the essential oil of Wedelia biflora (L) D.C. (Fam. Compositae) - Curaming, Rodrigo Carrion
The fresh leaves of Wedelia biflora (Linn.) DC. (Fam. Compositae) yielded approximately from 0.71% to 0.76% essential oil. Its moisture content was 83.4%. The oil gave a refreactice index (28°C) of 1.5989. the oil has an aromatic odor and slightly sweetish in taste. When freshly distilled, it is colorless, turning yellow on standing.